2016
DOI: 10.1111/aogs.12930
|View full text |Cite
|
Sign up to set email alerts
|

Uterine leiomyosarcoma – incidence, treatment, and the impact of morcellation. A nationwide cohort study

Abstract: The most frequent symptom in women suffering from LMS was abnormal uterine bleeding [110/212 (51.9%)]. LMS was histopathologically verified in 49/212 (23.1%) preoperatively. In 48/212 (22.6%), a malignant condition was suspected and they were treated accordingly. In 115/212 (54.2%), malignancy was not suspected at time of surgery and the women were treated according to the treatment protocol for fibroids. In only four patients was tissue retrieval by power morcellation conducted, accounting for 1.9% of all LMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…Overall, this simulation identified 29 genomic regions (10 amplifications and 19 deletions) for which the random chance of being affected by an SCNA twice was very low (p < 5.0E-03; supplementary Table S5). Interestingly, pathway analysis of genes located in these 29 regions revealed that the PTEN pathway (FDR 5 2.4E-02), the glioblastoma multiforme signaling pathway (FDR 5 3.6E-02) and the PI3K/AKT pathway (FDR 5 6.3E-02) were enriched (supplementary 1 For deleted (del) and amplified (amp) regions, only downregulated and upregulated genes were selected, respectively, in the regions identified in uLMS (FDR < 5E-02). Additional genes of interest were selected in the smallest region (overlap of uLMS and euLMS).…”
Section: Whole-genome Sequencing For In-depth Characterization Of Scnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, this simulation identified 29 genomic regions (10 amplifications and 19 deletions) for which the random chance of being affected by an SCNA twice was very low (p < 5.0E-03; supplementary Table S5). Interestingly, pathway analysis of genes located in these 29 regions revealed that the PTEN pathway (FDR 5 2.4E-02), the glioblastoma multiforme signaling pathway (FDR 5 3.6E-02) and the PI3K/AKT pathway (FDR 5 6.3E-02) were enriched (supplementary 1 For deleted (del) and amplified (amp) regions, only downregulated and upregulated genes were selected, respectively, in the regions identified in uLMS (FDR < 5E-02). Additional genes of interest were selected in the smallest region (overlap of uLMS and euLMS).…”
Section: Whole-genome Sequencing For In-depth Characterization Of Scnasmentioning
confidence: 99%
“…Uterine leiomyosarcomas (uLMS), arising from the myometrium, are rare malignancies with an annual incidence rate of 0.4-0.9/100,000 women. 1 Although prognosis depends on the stage, uLMS are generally aggressive tumors, with 5-year survival rates ranging from 16% for stage IV uLMS to 57% for stage I uLMS. 2 The cornerstone of treatment is hysterectomy with or without bilateral salpingo-oophorectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, a rare malignant sarcoma subtype, leiomyosarcoma (LMS) has many similar features to benign fibroids and may consequently escape diagnosis preoperatively. LMS accounts for approximately 1.9% of uterine cancers and has an estimated incidence of 0.36–0.86 per 100 000 women . Occult LMS in women surgically treated for presumed benign fibroids has been found to be 0.07–0.49% of cases .…”
Section: Introductionmentioning
confidence: 99%
“…The objective of Skorstad et al's [21] In 48/212 (22.6%), a malignant condition was suspected and they were treated accordingly. In 115/212 (54.2%), malignancy was not suspected at time of surgery and the women were treated according to the treatment protocol for fibroids.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, power morcellation of LMS has not lead to reduced survival. The authors suggest that power morcellators may be used in surgical treatment of selected cases of premenopausal women with symptomatic, presumed benign uterine leiomyomas [21].…”
Section: Discussionmentioning
confidence: 99%